2019
DOI: 10.2217/fon-2019-0068
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Mismatch Repair Deficiency in Prostate Cancer

Abstract: Immune checkpoint blockade holds great promise in the treatment of solid tumors but has not yet been approved for use in advanced prostate cancer. This is largely due to the relatively modest response in clinical trials in unselected patients and the lack of available biomarkers to predict clinical benefit. Germline and somatic mismatch repair (MMR) gene deficiencies are more prevalent than previously thought, especially in the metastatic setting, in patients with high-grade Gleason scores and in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 92 publications
0
21
0
1
Order By: Relevance
“…This inspired the development of ICIs or blockades that led to the revolutionary treatment of many cancer types and earned both James P Allison and Tasuku Honjo a 2018 Nobel Prize in Physiology or Medicine. Patients with melanoma, bladder and kidney cancers that exhibit mismatch repair deficiency (dMMR), cyclin dependent kinase 12 (CDK12) loss and high tumour mutational burden characterised by good T cell infiltration tend to respond well to ICIs as compared to patients with PCa [ 63 , 64 ]. PCa is generally immunologically “cold” associated with low tumour mutational burden around tumour microenvironment and enriched with poor T cell infiltration and myeloid cells that are immunosuppressive [ 65 , 66 ].…”
Section: Recap the Role Of Immune System In Pca And Advanced Stagesmentioning
confidence: 99%
“…This inspired the development of ICIs or blockades that led to the revolutionary treatment of many cancer types and earned both James P Allison and Tasuku Honjo a 2018 Nobel Prize in Physiology or Medicine. Patients with melanoma, bladder and kidney cancers that exhibit mismatch repair deficiency (dMMR), cyclin dependent kinase 12 (CDK12) loss and high tumour mutational burden characterised by good T cell infiltration tend to respond well to ICIs as compared to patients with PCa [ 63 , 64 ]. PCa is generally immunologically “cold” associated with low tumour mutational burden around tumour microenvironment and enriched with poor T cell infiltration and myeloid cells that are immunosuppressive [ 65 , 66 ].…”
Section: Recap the Role Of Immune System In Pca And Advanced Stagesmentioning
confidence: 99%
“…Concerning prostate cancer, MMRd has been identified in about 5% of metastatic patients and the most frequently mutated genes are MSH2 and MSH6 [ 73 ]. Only a small percentage of MMR gene mutations are inherited (germline), with Lynch syndrome being rarely associated with prostate cancer, thus meaning that MMRd could be acquired by prostate cancer cells during disease evolution [ 74 ].…”
Section: Predictive and Prognostic Markersmentioning
confidence: 99%
“…Mutations in MMR genes including MSH2 (MutS Homolog 2), MLH1 (MutL homolog 1), PMS1 (PMS1 homolog 1), PMS2 (PMS homolog 2) or MSH6 (MutS Homolog 6) subsequently give rise to a highly penetrant autosomal dominant predisposition cancer known as Lynch syndrome that increase risk for colon, endometrial, prostate, and other cancers. Several studies have shown deleterious mutations in these genes are causal of cancer development across populations ( 112 ). Matejcic and colleagues performed targeted gene sequencing, using a panel composed of 19 MMR precancer disposition genes, in 2,453 AA and 1,151 Ugandan Cases and Controls with prostate cancer.…”
Section: Hereditary Prostate Cancer Genesmentioning
confidence: 99%